Effectiveness of plant barriers on the isolation of cotton plots - Castro, Emílio da Maia de; Gridi-Papp, Imre Lagos; Paterniani, Ernesto (Pesquisa Agropecuaria Brasileira, 2014)
The effectiveness of plant barriers in reducing cross pollinization between adjacent plots of cotton (Gossypium hirsutum L.) was studied at the Sete Lagoas Experiment Station, Minas Gerais, during the growing seasons of 1973/74 and 1974/75. The barriers had 4 m of with, and the glandless cotton (gl2gl3) was used to determine the amount of natural crossings. All plant barriers used were effective in reducing the frequency of natural crossings, but corn was significantly better than sorghum, cotton and crotalaria. These did not differ among themselves although they ranked in the presented order. The corn reduced the contamination from 15,1 to 5,2%, approximately. When samples were taken from the first, second, third, fourth and fifth border lines of adjacent cotton plots, a linear decrease for natural crossing values was observed. The amount of natural cross fertilization for a given plant in the population was estimated to be about 32%.